The Chimera of the Real and Substantial Connection Test Special Issue: Symposium Honouring the Late Mr. Justice Kenneth Lysyk: Kenneth Lysyk as a Scholar: The Conflict of Laws - Blom, Joost; Edinger, Elizabeth (UBC Law Review, 2005)
Disclaimer: This summary was generated by AI based on the content of the source document.